Positioning of pivot points in quadrupedal locomotion: limbs global dynamics in four different dog breeds - Andrada, Emanuel; Hildebrandt, Gregor; Witte, Hartmut; Fischer, Martin S. (Frontiers in Bioengineering and Biotechnology, 2023)
Dogs (Canis familiaris) prefer the walk at lower speeds and the more economical trot at speeds ranging from 0.5 Fr up to 3 Fr. Important works helped to understand these gaits at the levels of center of mass, joint mechanics, and muscular control. However, less is known about the global dynamics for limbs and if these are gait or breed specific. For walk and trot, we analyzed dog global dynamics, based on motion capture and single leg kinetic data, recorded from treadmill locomotion of French Bulldog (N = 4), Whippet (N = 5), Malinois (N = 4) and Beagle (N = 5). Dog pelvic and thoracic axial leg functions combined compliance with leg lengthening. Thoracic limbs were stiffer than the pelvic ones and absorbed energy in the scapulothoracic joint. Dogs ground reaction forces (GRF) formed two virtual pivot points (VPP) during walk and trot each. One emerged for the thoracic (fore) limbs (VPPTL) and is roughly located above and caudally to the scapulothoracic joint. The second is located roughly above and cranially to the hip joint (VPPPL). The positions of VPPs and the patterns of the limbs` axial and tangential projections of the GRF were gait but not always breed related.When they existed, breed related changes were mainly exposed by the French Bulldog.During trot, positions of the VPPs tended to be closer to the hip joint or the scapulothoracic joint, and variability between and within breeds lessened compared to walk. In some dogs, VPPPL was located below the pelvis during trot. Further analyses revealed that leg length and not breed may better explain differences in the vertical position of VPPTL or in the horizontal position of VPPPL. Vertical position of VPPPL was only influenced by gait, while the horizontal position of VPPTL were not breed or gait related. Accordingly, torque profiles in the scapulothoracic joint were likely between breeds while hip torques profiles size related. In dogs, gait and leg length are likely the main VPPs positions' predictors. Thus, variations of VPP positions may follow reduction of limb work. Stability issues need to be addressed in further studies.